Diterpenes from Euphorbia piscatoria: Synergistic Interaction of Lathyranes with Doxorubicin on Resistant Cancer Cells - Reis, Mariana A.; Paterna, Angela; Mónico, Andreia; Molnar, Joseph; Lage, Hermann; Ferreira, Maria-José U. (Planta Medica, 2014)
Four new diterpenes were isolated from the methanolic extract of Euphorbia piscatoria, two ent-abietanes (1, 2) and two lathyrane-type macrocyclic diterpenes (3, 4), along with three known diterpenes (5–7). Their structures were characterized by spectroscopic methods, mainly 1D and 2D NMR (1H, 13C, DEPT, COSY, HMBC, HMQC, and NOESY) experiments. Compound 2, with an unusual structure, might be considered intermediate in the biosynthesis of ent-abietane α,β-unsaturated lactones, commonly found in Euphorbia species. Therefore, a possible biogenetic pathway is proposed. The MDR reversal potential of macrocyclic diterpenes 3–5 was evaluated through a drug combination assay, using the L5178Y mouse T lymphoma cell line transfected with the human MDR1 gene. Compounds 3–5 were able to enhance, synergistically, the antiproliferative activity of doxorubicin (combination indexes < 0.5). Moreover, compounds 1–6 were also assessed for their antiproliferative activity on human MDR cancer cell models, namely gastric, pancreatic, and colon. Weak antiproliferative activity was observed for compounds 1 (IC50 = 66.02 ± 7.10 µM) and 4 (IC50 = 39.51 ± 3.82 µM) on the MDR gastric cell line.
Keywords: Euphorbia piscatoria; Euphorbiaceae; lathyrane macrocyclic diterpenes; abietane lactones; MDR-reversal